Childhood adversities and risk for problematic alcohol use. (August 2016) - Dragan, Małgorzata; Hardt, Jochen
Abstract: The findings from studies exploring the relationship between childhood adversities (CAs) and adolescent and adult drinking problems are inconclusive – some researchers have found strong effects, others virtually none. In this study, we sought to examine the associations between 23 types of retrospectively reported CAs and adult problematic alcohol use in two samples, one drawn from Germany, the other from Poland. A total sample of 1008 participants was recruited via the internet: 500 in Germany and 508 in Poland. They completed a set of questionnaires including questions regarding various types of CA, and also the CAGE tool for the identification of problem drinking. CAs were grouped into four categories: Negative Personal Experience, Family Adversities, Parental Disorders, Parent-Child Relationships; this last category included role reversal. Separate logistic regression analyses were performed, with age, gender and country as potential confounders. The probability of having an alcohol problem was higher in men, and higher in Poland than in Germany. Of the risk factors tested, three displayed a significant association with problematic alcohol use. The risk factors concerned were Regular Arguments Between the Parents, plus two types of adversities from the Parent-Child Relationships cluster: Maternal Control and Maternal Role Reversal. The results serve to underline the importance of examining links between childhood risk factors and problematic alcohol use, and also suggest that certain less visible symptoms of a disordered parent-child (particularly mother-child) relationship, such as parentification, may constitute important risk factors for the development of drinking problems in later life. Highlights: Association between childhood adversities and problematic alcohol use was examined Regular arguments between parents were related to adult problematic alcohol use Maternal control and role reversal were associated with adult problematic alcohol use Parentification independently from parental drinking predicts adult problem drinking